Synthesis of Bi4Ti3O12 decussated nanoplates with enhanced piezocatalytic activity. Issue 44 (4th November 2019) - Wu, Jiang; Qin, Ni; Lin, Enzhu; Yuan, Baowei; Kang, Zihan; Bao, Dinghua
Abstract : Bi4 Ti3 O12 decussated nanoplates were successfully synthesized by a novel template hydrothermal method, which show an excellent piezocatalytic performance. Abstract : A variety of nanostructured Bi4 Ti3 O12 materials with diverse morphologies were synthesized by a novel hydrothermal method using layered titanate Na2 Ti3 O7 as a synthetic precursor. Among these materials, decussated nanoplates exhibit superior piezocatalytic activity compared with other piezocatalysts of the perovskite family. The enhanced piezocatalytic activity is attributed to the large piezoelectric potential difference and the short distance between polar surfaces, which may help enhance the driving force of charge transport. The finite element method (FEM) simulation of piezoelectric response in different Bi4 Ti3 O12 nanostructures was performed to illustrate the influence of morphological features on the piezocatalytic performance. The catalytic mechanism of Bi4 Ti3 O12 was investigated by the detection and characterization of free radicals and intermediate products with electron spin resonance (ESR) spin-trapping technique and liquid chromatography-mass spectrometry (LC-MS). This work may push forward the development of piezocatalytic materials, and provide insights into piezocatalysis for environmental applications.